Self-Assemblable Polymer Smart-Blocks for Temperature-Induced Injectable Hydrogel in Biomedical Applications - Hoang Thi, Thai Thanh; Sinh, Le Hoang; Huynh, Dai Phu; Nguyen, Dai Hai; Huynh, Cong (Frontiers in Chemistry, 2020)
Self-assembled temperature-induced injectable hydrogels have been widely investigated as drug delivery systems and platforms for tissue regeneration. Self-assemblable polymer smart-blocks play an important role in fabrication of hydrogels because they can self-assemble to induce the gelation of their copolymer in aqueous solution. The self-assembly happens due to the property transformations, such as hydrophobicity, ionization, and conformational change, in response to an external stimulus change, including temperature, pH, glucose, ionic strength, magnetic field, electric field, or their combination. The self-assemblable smart-block based copolymers exist as a solution in aqueous media at a certain condition that is suitable for mixing with bioactive molecules and/or cells. However, this solution turns into a hydrogel due to the self-assembly of the smart-blocks under exposure to the external stimulus change in vitro or being injected into the living body for controlling the release of loaded bioactive molecules or serving as biomaterials scaffolds for tissue regeneration. This work reports current scenery in development of these self-assemblable smart-blocks for fabrication of temperature-induced injectable hydrogels and their potential application as drug delivery systems and platforms for tissue engineering.